Analisis Pertimbangan Hakim dalam Mengabulkan Gugatan Perceraian Akibat Praktik Poligami (Studi Putusan Nomor 275/Pdt.G/2024/PA.Ska) - Husnul Zakiah; Muchlis Bahar; Elfia Elfia (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Polygamy in Islamic law is permissible provided that the husband is able to treat all wives fairly. Failure to fulfill this principle may lead to continuous marital disputes ending in divorce. This study aims to examine the judge's legal reasoning in granting a divorce petition due to polygamy in Decision Number 275/Pdt.G/2024/PA. Ska and to assess its conformity with the principle of justice in Islamic law and Indonesian positive law. This research employs normative legal research using statutory, conceptual, and case approaches. Data were collected through library research on legislation, court decisions, legal literature, and doctrines, and analyzed qualitatively. The findings indicate that the court granted the divorce based on continuous marital disputes as regulated under the Marriage Law, Government Regulation Number 9 of 1975, and the Compilation of Islamic Law. From the perspective of Islamic law, the decision is consistent with Qur'an Surah An-Nis?' verses 3 and 129, as well as Wahbah az-Zuhaili's view that justice constitutes the primary requirement for the permissibility of polygamy. Therefore, the divorce was granted because of the husband's failure to uphold justice rather than merely because of the existence of polygamy.